Alpine tectonic movements and salt tectonics of Eastern Ukraine - Goryainov, Sergey (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Within Eastern Ukraine, in the course of previous studies, neotectonic movements were established, caused by both salt tectonics and Attic (post-Miocene - pre-Pliocene) thrust dislocations of northeastern vergence. They are partially displayed in modern relief. The aim of the study was to reveal the structural results of the interaction of post-Pliocene fold-thrust deformations and modern salt tectonics of Eastern Ukraine. Research methodology. The base of the Cenozoic deposits of Eastern Ukraine was chosen as an indicator surface reflecting both those and other movements. Its initial orientation is horizontal. Deviations from the horizontal reflect the direction and amplitude of deformations. The morphology of this surface was depicted by isolines with a vertical step of 20 m. To build a map of the supporting surface, state geological maps and data from more than 2,100 wells drilled in this area were used. Research results. A map of the shape of the Cenozoic base in tectonic blocks between the Attic thrusts and beyond their development has been constructed. Uplifts of this surface, which are not associated with thrust movements, have been revealed. The dimensions of such uplifts are 8÷30 × 6÷15 km with vertical amplitude of 40 - 100 m or more. The uplifts are usually contoured by ring or arc compensation troughs a few kilometers wide and 20-100 m deep. Some of these uplifts are associated with the known salt domes of the area. Other uplifts do not contain such domes. It is possible that they formed over salt "pillows", which did not have enough salt reserves to form salt diapirs. The area of distribution of such uplifts approximately corresponds to the area of distribution of Devonian salt deposits at a depth of 5-10 km or more. Scientific novelty. Neotectonic uplifts were discovered, similar in shape and size to those caused by salt tectonics, but located outside the areas of distribution of known salt-bearing strata. It is hypothesized that this is related to the older Hercynian overthrusts. The uplifts are located above the hanging blocks of the Hercynian overthrusts in the north and south of the study area. These thrusts were formed on the northern and southern sides of the former Dnieper-Donetsk depression during its destruction by the Hercynian folding. It is possible that the nappes over thrusts the Devonian salt-bearing deposits with metamorphic rocks of the crystalline basement. The decrease in the level of the World Ocean in the Quaternary period further increased the lithostatic load on the salt-bearing strata. This activated the isostatic upwelling of salt and the formation of gently sloping neotectonic uplifts. Practical significance. These results clarify the geological structure of the territory and make it possible to expand the area of hydrocarbon prospecting.